Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.actamat.2016.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Widmanstätten ferrite at very high temperatures in the austenite phase field

Abstract: Compression tests were carried out on a 0.06wt%C-0.3wt%Mn-0.01wt%Si steel at temperatures high in the austenite phase field. Eight deformation temperatures were selected in the range from 1000 to 1350 ⁰C at 50 ⁰C intervals. The quenched samples were examined using optical microscopy and EBSD techniques. It was observed that dynamic transformation took place and that the volume fraction of transformed ferrite first decreased with temperature (up to 1050 ⁰C) and then increased as the delta ferrite temperature do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 27 publications
7
44
1
Order By: Relevance
“…Under these conditions, an equivalent strain of one is again consistent with the experimental data, as shown below for the present steel, as well as for the other steels that have been examined to date [7]. C. Aranas Jr. et al: A metastable phase diagram for the dynamic transformation of austenite above the Ae 3 [3]. This was calculated using the FSstel database of the FactSage thermodynamic software [11].…”
Section: The Driving Force For Dynamic Transformationsupporting
confidence: 63%
See 2 more Smart Citations
“…Under these conditions, an equivalent strain of one is again consistent with the experimental data, as shown below for the present steel, as well as for the other steels that have been examined to date [7]. C. Aranas Jr. et al: A metastable phase diagram for the dynamic transformation of austenite above the Ae 3 [3]. This was calculated using the FSstel database of the FactSage thermodynamic software [11].…”
Section: The Driving Force For Dynamic Transformationsupporting
confidence: 63%
“…It was shown in earlier work [3] that dynamic transformation can be initiated up to 480 8C above the paraequilibrium C. Aranas Jr. et al: A metastable phase diagram for the dynamic transformation of austenite above the Ae 3 The total accommodation work represented by the sum of Fig. 5a and b plotted against temperature.…”
Section: Metastable Fe-c Binary Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] This has been shown to occur throughout the austenite phase field. 8,9) In earlier publications, the present authors have reported that the amounts of ferrite formed per pass increase with decreasing temperature. 9,10) Subsequently, the metastable ferrite tends to retransform to austenite to an extent that increases with the length of the interpass interval.…”
Section: Introductionmentioning
confidence: 94%
“…3) More recently Basabe et al, 4) conducted torsion tests on a 0.036% Nb microalloyed steel and reported that both the forward and the reverse transformation were retarded by the addition of niobium. In some follow-up experiments, Grewal et al 5) showed that ferrite can be formed everywhere within the austenite phase field.…”
Section: Introductionmentioning
confidence: 99%